Co-administration of Rauwolfia vomitoria with Gongronema latifolium or Vernonia amygdalina on spatial learning, memory, and some bio-molecules - Ekong, Moses B; Peter, Aniekan I; Ekpene, Ubong U (Asian Journal of Medical Sciences, 2015)
Background: Rauwolfia vomitoria is a plant with sedative properties found useful in the management of psychotic disorders, with adverse effects being reported on its use in different brain areas. Aims and Objectives: To investigate the acute effect of combination of Rauwolfia vomitoria with either Gongronema latifolium or Vernonia amygdalina on spatial learning and memory, and some bio-molecules in rats. Materials and Methods: 24 adult male Wistar rats weighing between 220 g - 300 g were equally divided into four groups (1-4). Group 1 animals were the control treated with 0.5 ml of Tween 20. Groups 2, 3 and 4 animals were administered respectively; 150 mg/kg of R. vomitoria, a combination of 150 mg/kg of R. vomitoria and 200 mg/kg of G. latifolium, and a combination of 150 mg/kg of R. vomitoria and 200 mg/kg of V. amygdalina for seven days. On days 4-7 concurrent with treatment, spatial learning and memory test was carried out using the Morris water maze, and the animals were sacrificed twelve hours after the last treatment. Their sera were used for enzyme and other bio-molecules analysis. Results: There was no difference in spatial learning and memory. The activities of aspartate aminotransferase, alanine aminotransferase and alkaline phosphatase, and the serum cholesterol and triglycerides levels were also not different compared to the control group. Conclusion: The dose and duration of administration of the extract of R. vomitoria either alone, or in combination with G. latifolium or V. amygdalina may not affect spatial learning or memory, or alter serum biomolecules. Asian Journal of Medical Sciences Vol.7(1) 2015 82-87